Randomized Trial of Anti-inflammatory Medications and Coronary Endothelial Dysfunction in Patients With Stable Coronary Disease - Hays, Allison G.; Schär, Michael; Bonanno, Gabriele; Lai, Shenghan; Meyer, Joseph; Afework, Yohannes; Steinberg, Angela; Stradley, Samuel; Gerstenblith, Gary; Weiss, Robert G. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Inflammation plays a critical role in the pathogenesis of coronary artery disease (CAD), however the impact of anti-inflammatory therapies to reduce those processes which promote atherosclerosis in CAD patients is unknown. We aimed to test the hypothesis that anti-inflammatory approaches improve impaired coronary endothelial function (CEF), a driver of coronary atherosclerosis, in stable CAD patients. Methods and Results: We performed a single-center, randomized, placebo-controlled, double-blinded trial to assess whether low dose methotrexate (MTX), low dose colchicine (LDC) and/or their combination (MTX+LDC), improves CEF using non-invasive MRI measures in patients with stable CAD (N=94). The primary endpoint was the MRI-detected change in coronary cross-sectional area from rest to isometric handgrip exercise (IHE), a predominantly nitric oxide-dependent endothelial dependent stressor. Coronary and systemic endothelial endpoints, and serum inflammatory markers, were collected at baseline, 8 and 24 weeks. Anti-inflammatory study drugs were well tolerated. There were no significant differences in any of the CEF parameters among the four groups (MTX, LDC, MTX+LDC, placebo) at 8 or 24 weeks. Serum markers of inflammation and systemic endothelial function measures were also not significantly different among the groups at 8 and 24 weeks compared to baseline. Conclusion: This is the first study to examine the effects of the anti-inflammatory approaches using MTX, LDC and/or the combination in stable CAD patients on CEF, a marker of vascular health and the primary endpoint of the study. Although these anti-inflammatory approaches were relatively well tolerated, they did not improve coronary endothelial function in patients with stable CAD.